A regulamentação do teletrabalho no Brasil: antinomias e interpretações corretivas à luz do Direito argentino - Teixeira, Winston de Araújo (2023)
In the exposition of its purpose, the bill that would later regulate telework stated that its objective was the modernisation of labour legislation as a response to the socioeconomic evolution in Brazil. Yet, the changes in the Consolidation of Labour Laws (CLT) still generate legal uncertainty since the concept and rights of teleworkers conflict, in some points, with the rights guaranteed to other employees. In that regard, it is unclear whether the norms that regulate telework are compatible with the legal system in Brazil? Hypothetically, telework regulated in Brazil does not comply with the legal order because it presents antinomies or conflicts. This research aims to: (1) analyse the regulation of teleworking based on the CLT; (2) discuss the impacts of the changes caused by this regulation, mainly those related to working hours, control of working hours, equipment and infrastructure costs, responsibility for risks arising from work accidents, negotiation and amendment of the teleworking contract and the right to disconnect; (3) verify the compatibility of telework with others that make up the Brazilian legal system; and (4) compare the Brazilian and Argentinian legislations that deal with telework. To achieve these objectives, this research uses the inductive method, starting from the study of telework, identifying its characteristics and particularities; then the research analyses possible incompatibilities with the labour legislation applied generically to other employment contracts that are ruled by the CLT. To identify the incompatibilities, Norberto Bobbio's thesis on the legal system, supported by the ideas of the staggered hierarchy of Hans Kelsen, was used as a theoretical framework. After the inconsistencies were identified, the comparative method was used to find in the Argentine legislation possible suggestions to face the normative conflict within the scope of the internal order. Finally, it was concluded that workers' rights are fundamental social rights and, for that reason, they enjoy special protection; therefore, the legislative changes in the CLT, promoted by Laws nº. 13,467/2017 and nº 14,442/2022, especially the item III of article 62, the articles 75-A to 75-F and the item VIII of article 611-A must integrate and complete the order, in compliance with the hierarchy of norms for workers’ protection and social justice, since the identified inconsistencies can be resolved by the role of the interpreter (legislator or judge) without necessarily eliminating existing norms.